PENURUNAN KADAR MIKROPLASTIK PADA AIR KALI WONOKROMO DENGAN METODE ELEKTROKOAGULASI - Dila Rahmayanti; Firra Rosariawari (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The abundance of microplastics in Surabaya's surface water can disrupt the sustainability of the river ecosystem and have a bad impact on humans. Because most of the raw water used by the people of Surabaya comes from surface water. Microplastics less than 5µm in size contain hazardous chemicals such as Polycroline Binefil (PCB) and are toxic. Microplastics can carry heavy metals and also some pathogenic microorganisms that attach to the microplastic body, this can possibly enter the bloodstream and infect the body. One of the processing alternatives that can be used to reduce microplastic levels is to use electrocoagulation. Electrocoagulation is the process of clumping and depositing fine particles in water using electrical energy. Microplastics contained in water are removed through a process of flocculation and deposition. This study aims to determine the effectiveness of reducing levels of microplastics using electrocoagulation with variations in the distance between electrodes and detention time. The variation of the distance between the electrodes used was 1.5 cm; 2 cm; 3cm; and 5 cm. From the research conducted, it was found that in order to reduce the microplastic levels in surface water samples, the most effective distance between electrodes was 3 cm with a decrease in microplastic levels by 89%.